A practical risk scale for predicting morbidity and mortality in the emergency general surgical setting: A prospective multi-center study. (December 2018) - Ablett, A.D.; McCarthy, K.; Carter, B.; Pearce, L.; Stechman, M.; Moug, S.; Ceelen, W.; Hewitt, J.; Myint, P.K.; ,
Abstract: Background: Low albumin is a prognostic factor associated with poor surgical outcomes. We aimed to examine the predicative ability of easily obtainable point-of-care variables in combination, to derive a practical risk scale for predicting older adults at risk of poor outcomes on admission to the emergency general surgical setting. Methods: This is an international multi-center prospective cohort study conducted as part of the Older Persons Surgical Outcomes Collaboration (www.OPSOC.eu ). The effect of having hypoalbuminemia (defined as albumin ≤3.5 g/dL) on selected outcomes was examined using fully adjusted multivariable models. In a subgroup of patients with hypoalbuminemia, we observed four risk characteristics (Male, Anemia, Low albumin, Eighty-five and over [MALE]). Subsequently, the impact of incremental increase in MALE score (each characteristic scoring 1 point (maximum score 4) on measured outcomes was assessed. Results: The cohort consisted of 1406 older patients with median (IQR) age of 76 (70–83) years. In fully adjusted models, hypoalbuminemia was significantly associated with undergoing emergency surgery (1.32 (95%CI 1.03–1.70); p = 0.03), 30-day mortality (4.23 (2.22–8.08); p < 0.001), 90-day mortality (3.36 (2.14–5.28); p < 0.001) (primary outcome), and increased hospital length of stay, irrespective of whether a patient received emergency surgical intervention. Every point increase in MALE score was associated with higher odds of mortality, with a MALE score of 4 being associated with 30-day mortality (adjusted OR(95% CI) = 33.38 (3.86–288.7); p = 0.001) and 90-day mortality (11.37 (3.85–33.59); p < 0.001) compared to the reference category of those with MALE score 0. Conclusions: The easy to use and practical MALE risk score calculated at point of care identifies older adults at a greater risk of poor outcomes, thereby allowing clinicians to prioritize patients who may benefit from early comprehensive geriatric assessment in the emergency general surgical setting. Highlights: MALE score identifies older adults at an increased risk of poor outcomes on admission to the emergency surgical setting. MALE score is based upon four easily obtainable characteristics often collected at the point-of-care. We demonstrated the linear relationship between incremental increase in MALE score point and poor outcomes. MALE scores for patients are quick and easy to calculate.